2004
DOI: 10.1063/1.1759297
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chaotic saddles in high-dimensional dynamical systems: The Kuramoto–Sivashinsky equation

Abstract: This paper presents a methodology to study the role played by nonattracting chaotic sets called chaotic saddles in chaotic transitions of high-dimensional dynamical systems. Our methodology is applied to the Kuramoto-Sivashinsky equation, a reaction-diffusion partial differential equation. The paper describes a novel technique that uses the stable manifold of a chaotic saddle to characterize the homoclinic tangency responsible for an interior crisis, a chaotic transition that results in the enlargement of a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…Finally ∈ [0.1, 0.45] [25]. The equation was solved numerically using the pseudo-spectral method [31,32] and a 12 th order predictor-corrector Adams integrator [33], with time step h = 10 −2 , and a total of N = 64 Fourier modes were simulated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Finally ∈ [0.1, 0.45] [25]. The equation was solved numerically using the pseudo-spectral method [31,32] and a 12 th order predictor-corrector Adams integrator [33], with time step h = 10 −2 , and a total of N = 64 Fourier modes were simulated.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Of particular interest for periodic domains (2) are the Galilean invariance, u(x, t) → u(x − ct, t) + c for all speeds c, and the spatial translation invariance, u(x, t) → u(x + d, t) for all d. These two symmetries do not hold for odd-periodic domains (3). The Kuramoto-Sivashinsky pde (1) with oddperiodic domains (3) is particularly well studied (e.g., Rempel et al 2004;Lan and Cvitanović 2008;Foias et al 1986;Eguíluz et al 1999) compared to that with periodic domains, as the removal of periodic symmetries simplifies somewhat the analysis of the dynamics. The relatively simpler dynamics of the odd-periodic case is observed in Section 3 when comparing the periodic and odd-periodic Lyapunov spectra.…”
Section: The Kuramoto-sivashinsky Equationmentioning
confidence: 99%
“…This periodic window ends with an interior crisis (IC) at a IC =0.330248. To plot the chaotic saddle, for each value of a, we plot a straddle trajectory close to the chaotic saddle using the PIM triple algorithm with a precision of 10 −6 (Nusse and York, 1989;Rempel and Chian, 2004;Rempel et al, 2004a). The blue region inside the periodic window in Fig.…”
Section: Alfvén Chaosmentioning
confidence: 99%
“…Kawahara and Kida (2001) numerically found an unstable periodic orbit in a three-dimensional plane Couette turbulence described by the incompressible Navier-Stokes equation. (Chian et al, 2002) and Rempel et al (2004a) showed that unstable periodic orbits and chaotic saddles can characterize an interior crisis and the intermittency induced by an interior crisis in the Kuramoto-Sivashinsky equation. Faisst and Eckhard (2003) identified a family of unstable traveling waves originating from saddle-node bifurcations in a Published by Copernicus GmbH on behalf of the European Geosciences Union and the American Geophysical Union.…”
Section: Introductionmentioning
confidence: 99%